Responses to phosphate deprivation in white clover (Trifolium repens L.) : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Plant Biology at Massey University - Effendy, Jollanda (Massey University, 2007)
Four breeding lines of white clover (Trifolium repens L.) were obtained from AgResearch Grasslands, Palmerston North, New Zealand, that had been shown previously to differ in terms of specific growth responses to added phosphate (P) in the field. These were designated Breeding Line (BL) 43 (low performer on low P; low performer on high P), BL 45 (low performer on low P; high performer on high P), BL 47 (high performer on low P; high performer on high P), and BL 49 (high performer on low P; low performer on high P). These breeding lines and five selected genotypes that were propagated from each line (designated 43-7, 43-8. 45-14. 45-4 and 47-9) were rooted in half-strength Hoagland solution in vermiculite for two weeks and then transferred to half-strength Hoagland liquid media for five weeks prior to the initiation of the experiments. For the breeding line screening, plants were acclimatized in a constant temperature environment for one week prior to treatments, while for the genotypic screening, plants were maintained in a temperature-controlled glasshouse. These lines and genotypes were characterized in relation to P uptake and utilization efficiency by growing in P-sufficient media (+P; 0.5 mM KH2PO4) and P-deficient media (-P; 0 mM KH2PO4) for 3, 5, 7 and 14 days (for the breeding line screening) and 7, 14 and 21 days (for the genotype screening). Over the time course, inorganic phosphate (Pi) content in leaves, non-specific acid phosphatase (APase) activity in intact roots (both as a total soluble activity and a cell-wall-associated activity), isoenzyme analyses, shoot dry weight (DW) and fresh weight (FW), leaf area, weight of an individual leaf (designated as the weight of the first fully expanded leaf), root FW, and the root:shoot (R:S) ratio were determined. Pi deprivation enhanced the induction of one major low mobility cell wall acidic isoform, two minor high mobility cell wall acidic isoforms and one major low mobility cell wall basic isoform in all genotypes. Furthermore, the activity of one major low mobility cell wall basic isoform was more higher in genotype 45-14 and one minor high mobility cell wall basic isoform was induced only in genotype 45-14 in response to Pi deprivation. In terms of individual BLs and genotypes, the screening results showed that BL 49 and genotype 45-14 displayed a constant Pi content and a slow induction of APase activity in the -P media, and had the highest total biomass FW in both +P and -P media. Overall (in both treatments) BL 49 and genotype 45-14 are the most efficient at utilizing available P as they produced the largest biomass FW, produced more roots in P- deprived media when compared with the other BLs and genotypes, and were more efficient in utilizing the P for the synthesis of biomass. BLs 43 and 45 and genotypes 43-7 and 43-8 are less efficient at utilizing available P, while under P deprivation, BL 45 and genotype 45-14 are the most efficient at utilizing P compared to the other BLs and genotypes. The study also showed that the Pi content in leaves and APase activity in roots was found to be the plant parameter most sensitive to Pi deprivation, and the results suggest that the selection of white clover germplasm for satisfactory performance under low P availability can be carried out using these two parameters as criteria.
Keywords: Phosphate deficiency diseases plants; White clover - Physiology; White clover -- Effect of phosphorus on